2012
DOI: 10.1371/journal.pone.0042101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of GABAA Receptor α Subunit Isoforms on the Benzodiazepine Binding Site

Abstract: Classical benzodiazepines, such as diazepam, interact with αxβ2γ2 GABAA receptors, x = 1, 2, 3, 5 and modulate their function. Modulation of different receptor isoforms probably results in selective behavioural effects as sedation and anxiolysis. Knowledge of differences in the structure of the binding pocket in different receptor isoforms is of interest for the generation of isoform-specific ligands. We studied here the interaction of the covalently reacting diazepam analogue 3-NCS with α1S204Cβ2γ2, α1S205Cβ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Loop C, on the other hand, has long been known to be important for ligand binding, since it is more variable than the other loops (Michalowski et al, 2017). α1-serine 206 (neighboring the serine mutated in our study) seems to interact physically with diazepam (Luscher et al, 2012). Both α1-serine 206 as well as α1-tyrosine 209 are important in determining the binding affinities for ligands of the benzodiazepine binding (Buhr et al, 1997) and S206 has been shown to influence the efficacy of midazolam to modulate GABA induced currents (Moody and Jenkins, 2018) as well as the affinities for β-carboline binding (Derry et al, 2004).…”
Section: Figurementioning
confidence: 61%
“…Loop C, on the other hand, has long been known to be important for ligand binding, since it is more variable than the other loops (Michalowski et al, 2017). α1-serine 206 (neighboring the serine mutated in our study) seems to interact physically with diazepam (Luscher et al, 2012). Both α1-serine 206 as well as α1-tyrosine 209 are important in determining the binding affinities for ligands of the benzodiazepine binding (Buhr et al, 1997) and S206 has been shown to influence the efficacy of midazolam to modulate GABA induced currents (Moody and Jenkins, 2018) as well as the affinities for β-carboline binding (Derry et al, 2004).…”
Section: Figurementioning
confidence: 61%
“…Compounds were applied for 20 s. None of the compounds could open the channel without GABA, so they all are only modulators of the channel. For details on the electrophysiological recordings see Lüscher et al 23 …”
mentioning
confidence: 99%
“…Previous studies found that the α6(Asn204) and α4(Ile203) residues (both homologous to human α1(Ser206)) were important for distinguishing the binding of negative benzodiazepines . Ser206 also physically interacts with diazepam in α1, α2 and α5, suggesting a critical role in benzodiazepine action . However, a neighboring mutation, homologous to α1(T207C), specifically altered benzodiazepine efficacy and not binding .…”
Section: Discussionmentioning
confidence: 99%
“…and α5, suggesting a critical role in benzodiazepine action. 37 However, a neighboring mutation, homologous to α1(T207C), specifically altered benzodiazepine efficacy and not binding. 12 We propose that the homologous Ser206 in loop C may provide an important point of contact between the ligand and benzodiazepine site that affects the coupling of the benzodiazepine site to GABA activation, thereby affecting the benzodiazepine's efficacy.…”
Section: Discussionmentioning
confidence: 99%